Experimental investigation of the effect of tribological performance of reduced graphene oxide additive added into engine oil on gasoline engine wear - Kaleli, Emrullah Hakan; Demirtas, Selman (WILEY, 2023)
Good dispersion stability of engine oil added with graphene is the premise of playing its superior tribology property and also the novelty of this study. As the tribological behaviour of a commercialised, fully synthetic 5W40 engine oil upon the incorporation of reduced graphene oxide in sample (0.02 wt%) like (5W40 engine oil + 0.02 wt% Reduced Graphene Oxide) called rGO6 presented superior tribological properties by exhibiting the lowest COF value in our previous work, the same sample was evaluated through a reciprocating tribometer, using steel ball (100 CR6) on a real polished gasoline engine cylinder liner with 5W-40 engine oil to investigate their wear and friction behaviour in boundary lubrication regime. It was found that a rGO6 nano-additive played an active role in lowering the coefficient of friction (3.29%) and increased surface protection by forming a protective layer on a smooth nanorough on rubbing surfaces.
Keywords: dispersion; friction; roughness; reduced graphene oxide; Engineering